Agricultural policies for sustainable management and use of natural resources in Africa - International Institute of Tropical Agriculture; Food and Agriculture Organization of the United Nations (2000)
World per capita food production is today estimated to be about 18% above what it was 30 years ago, but much of Africa is nutritionally worse off today than it was then. Since the vast majority of the poor in Africa depend on agriculture, increasing food production is among the principal means of combating poverty and malnutrition in Africa. The need to rapidly transform agriculture in Africa is understood by the fact that Africa's population growth rate of about 3% per year threatens to reduce the availability of natural resources per capita. Given the dominance of the agricultural sector in Africa (40% of GDP in 1997), it is generally accepted that without significant improvement in the sector performance, it will be inconceivable for Africa to achieve its growth target. Available evidence in Africa suggests that the last three decades have been characterized, among other things, by significant degradation of the natural resources base. One of the cause of this unfortunate situation is the serious difficulties policy makers in the most countries encounter in designing and implementing policies that could promote a widespread gender- sensitive adoption of agricultural technologies and practices that are not only productivity improving, but also environmentally sustainable. Africa's mission on how to achieve its policy objectives should consist of a program which as its focus sustainable agriculture and rural development, necessitating structural transformation in order to enhance production, improve food security, and reduce poverty. This process should be conceived as a comprehensive development approach where the criteria of efficiency, equity, and sustainability are carefully integrated within the coherent and operational framework. The integration of such areas as environment, rural development and structural transformation, and population and human settlements, should reflect the interactions of these major areas of concern as a matrix to promote sustainability.